STRATEGI PROMOSI DALAM MENINGKATKAN TAMU HOTEL GRAND BARUMBAY SAMARINDA SEBERANG - Yovan Ferdian (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
Precisely on the opposite side of Samarinda City which limits the flow of the Mahakam river, Grand Barumbay Hotel Samarinda Seberang is one of the resort hotels that has its own unique characteristics located in Samarinda Seberang. The purpose of this research is to find out and identify how the hotel promotion strategy in increasing Grand Barumbay hotel guests and what are the obstacles faced by the manager in promoting the Grand Barumbay Hotel Samarinda. This study aims to determine the hotel promotion strategy in increasing the number of guests visiting the Grand Barumbay hotel, Samarinda opposite. This type of research is qualitative. Sources of research data are key informants and informants. Data collection techniques in this research are in the form of observation, interviews, documentation, and literature study. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Grand Barumbay Samarinda Hotel Promotion Strategy is running with a promotional strategy that is applied, namely the marketing mix which includes Advertising, Personal Selling, Publicity, and Sales Promotion. The conclusion in this study is that the Personal Selling of the Grand Barumbay Samarinda hotel opposite is not in accordance with the theory because it is inefficient in promoting a hotel because of its individual nature in offering a product or service personally, Advertising, Publicity and Sales Promotion of Grand Barumbay Samarinda Hotel are in accordance with the theory, for hotel promotions, it is expected to update the latest promotional advertisements, create separate social media, especially Instagram and collaborate with tourism agencies or institutions for example travel, tourist attractions, tourism offices, organizations, and companies, and improve again in terms of appearance the front view of the hotel which can be seen clearly and attractively when viewed, especially guests or hotel visitors.